Explaining the effect of rapid internationalization on horizontal foreign divestment in the retail sector: An extended Penrosean perspective - Mohr, Alex; Batsakis, Georgios; Stone, Zita (Journal of International Business Studies, 2018)
We adopt a Penrosean perspective to study the effect of rapid international expansion on the subsequent divestment of international operations. We draw on regional strategy theory and differentiate Penrosean managerial resources by their geographical fungibility to argue that the effect of rapid international expansion on the divestment of international operations varies with the regional patterns of firms’ international expansion and international experience. We test our hypotheses using two-stage least squares (2SLS) estimation on data that capture the international expansion and divestment of retailers over the period 2003–2012.